Hierarchical core–shell nanoplatforms constructed from Fe3O4@C and metal–organic frameworks with excellent bilirubin removal performance. Issue 28 (10th June 2021) - Gan, Na; Sun, Qiaomei; Zhao, Ludan; Zhang, Shuangshuang; Suo, Zili; Wang, Xinlong; Li, Hui
Abstract : A novel core–shell nanoplatform based on Fe3 O4 @C and Uio66-NH2 was prepared. The excellent bilirubin removal performance, good separability, recyclability, cytotoxicity and hemocompatibility offer it great potential in hemoperfusion therapy. Abstract : Hemoperfusion has become the third-generation treatment strategy for patients suffering from hyperbilirubinemia, but adsorbents used for bilirubin removal mostly face intractable problems, such as unsatisfactory adsorption performance and poor hemocompatibility. Metal–organic frameworks (MOFs) are promising adsorbents for hemoperfusion due to their high specific surface areas and easily modified organic ligands. However, their microporous properties and separation have hampered their application. Here, a novel hierarchical core–shell nanoplatform (named Double-PEG) with tailored binding sites and pore sizes based on Fe3 O4 @C and Uio66-NH2 was constructed. Notably, Double-PEG showed excellent bilirubin uptake of up to 1738.30 mg g −1 and maintained excellent bilirubin removal efficiency in simulated biological solutions. A study on the adsorption mechanism showed that the adsorption of Double-PEG towards bilirubin tended to be chemical adsorption and in accordance with the Langmuir model. Besides, the good separability, recyclability, cytotoxicity and hemocompatibility of Double-PEG show great potential in hemoperfusion therapy. The finding of this study may provide a novel insight into the application of MOF materials in the field of hemoperfusion.